Impacts of Solution -Focused Group Counseling on Student's Self - Regulation and Scholastic Accomplishment: Examining the Effects of Solution-Focused Group Counseling on Student's Self-Regulation and Academic Success (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The motivation behind this study was to investigate theadequacy of result-centered advising on selfregulation besides scholarlyaccomplishment of secondary school scholars. Result-centered advising wasassessed through control and exploratory pretest – posttest bunch plan. Afterseven sessions group counseling with learners, the self–regulation andscholarly accomplishment of scholars in the advising mediation gathering werefundamentally expanded. In addition, the discoveries demonstrated huge contrastbetween control amass and trial amass in posttest outcomes (p < 0/05).